The quality of university services: reflections from a case study in the latin american context - Mejías Acosta, Agustín (2013)
The objective of this research is to identify factors that determine the quality of academic services in universities , from three case studies in the context of Latin America ( Venezuela , Mexico and Chile). Model survey SERVQUALing was used , and upon proof of sampling adequacy, the multivariate statistical technique of Factor Analysis , where the dimensions underlying quality of services as perceived by students were identified was used highlighting Safety , Responsiveness and Empathy as a key and common elements. The survey used was reliable and valid , as evidenced by the statistical tests performed ( significant at 5%). The results confirm the dynamic and multidimensional nature of quality of academic services , allowing present some thoughts for discussion.